AUTHENTIC NARRATIVE TEXTS IN ENGLISH TRANSLATION VERSION OF HOLY QURAN: A GENRE-BASED APPROACH - Puji Sumarsono (University of Kuningan, 2018)
Language exposure is crucial for beginners or students who learn English as their second or foreign language. Students are difficult to directly speak and write English if they never hear English conversation or monologue and never see the product of English in term of result of writing. Text as a product of writing is available and easily accessed around us. This circumstance, consequently, insists the ease use of reliable teaching material and effective teaching reading. As it was found in Australia and also the author experience, when teacher had students to freely write, 90% of the students wrote recount and narrative texts. Narrative texts have important role of narrative that every word in narrative is potentially memorable and possible to contribute to understanding text easily. In fact, it was found that there are many narrative texts in English translation of Holy Qur’an. However, they have their own typical.Keywords: authentic, English translation of Holy Qur’an, genre-based approach, narrative text